Persistent dysgeusia post-halitosis treatment: How does it impact the patients’ quality of life? - Carvalho, Bruna-Fernandes-Do Carmo [UNESP]; Alves, Mônica-Ghislaine-Oliveira; Dutra, Marignês-Theotonio-Dos Santos [UNESP]; Balducci, Ivan [UNESP]; Nicodemo, Denise [UNESP]; Almeida, Janete-Dias [UNESP] (My University, 2019)
Background: The objective of this study was to evaluate the quality of life and the presence of anxiety and depression in patients with dysgeusia post halitosis treatment. Material and Methods: Sixty patients were divided into three groups: Dysgeusia group (DG); Halitosis group (HG) and Control group (CG). The following instruments were used: Medical results study Short form health research of 36 items (SF-36), State-state anxiety inventory (STAI) and Self-report questionnaire-20 (SRQ-20). Results: Of the 60 subjects studied, 85% were female and 15% were male. The evaluation of SF-36 indicated a statistically significant correlation between some domains for DG and showed low scores for Mental Health. In relation to HG, low scores were obtained for Bodily Pain, Vitality and Emotional Role. The CG showed low scores for Bodily Pain, General Health and Vitality. STAI was significant when DG was compared to HG and CG. The mean SRQ-20 score was higher in DG compared with the other groups. Conclusions: Persistent dysgeusia post-halitosis treatment impacts on QoL generically in the Mental health domain, and specifically in trait and state anxiety. Symptoms of depression were also seen in this group of patients.
Keywords: Anxiety; Depression; Dysgeusia; Halitosis; Oral health; Quality of life